Maternal near-miss and mortality associated with hypertensive disorders of pregnancy remote from term: a multicenter observational study in GhanaAJOG Global Reports at a Glance - Katja C.E. Drechsel, MD; Kwame Adu-Bonsaffoh, MD, MPhil, MSc, FWACS (OBGYN); Klaartje M. Olde Loohuis, MD; Emmanuel K. Srofenyoh, MD, MPhil, FWACS (OBGYN); Daniel Boateng, PhD; Joyce L. Browne, MD, PhD (Elsevier, 2022)
BACKGROUND: Maternal death rates remain high in many low- and middle-income countries. Hypertensive disorders of pregnancy account for 18% of maternal mortality in Ghana. The maternal near-miss approach was designed to evaluate severe (acute) complications in pregnancy, which is useful to detect potential areas for clinical care improvement. OBJECTIVE: This study aimed (1) to determine the incidence of severe maternal complications, maternal near-miss cases, and mortality cases associated with hypertensive disorders of pregnancy remote from term and (2) to assess the health system's performance indicators for the management of hypertensive disorders of pregnancy remote from term in middle-income country referral hospitals. STUDY DESIGN: This study was nested in the ongoing Severe Preeclampsia adverse Outcome Triage study, a multicenter observational cohort study, and included women recruited from December 1, 2017, to May 31, 2020, from 5 referral hospitals in Ghana. Women aged >16 years, admitted to the hospital with hypertensive disorders of pregnancy, with gestational age between 26 and 34 weeks were eligible. Near miss was defined according to the World Health Organization and sub-Saharan African near-miss criteria. Descriptive statistics of pregnancy and maternal and perinatal outcomes up to 6 weeks after delivery of women with severe maternal outcomes were presented for maternal deaths and maternal near-miss casigurees and compared with that of women without severe maternal outcomes. The health system's maternal and perinatal performance indicators were calculated. RESULTS: Overall, 447 women with hypertensive disorders of pregnancy were included in the analyses with a mean maternal age of 32 (±5.8) years and mean gestational age at recruitment of 30.5 (±2.4) weeks. Of these patients, 46 (10%) had gestational hypertension, 338 (76%) had preeclampsia, and 63 (14%) had eclampsia. There were 148 near-miss cases (33.1%) and 12 maternal deaths (2.7%). Severe maternal outcomes constituted complications from severe preeclampsia (80/160 [50%]) and eclampsia (63/160 [39.4%]). Concerning organ dysfunction, hematologic and respiratory dysfunctions constituted 59/160 [38.6%] and 23/160 [14.8%] respectively. Nearly all women had a cesarean delivery (347/447 [84%] and 140/160 [93%] in the severe maternal outcome group) and delivered prematurely (83%, with 178/379 [93%] at <32 weeks of gestation). Stillbirth and neonatal deaths occurred in 63 of 455 women (14%) and 81 of 392 women (19%), respectively, constituting a stillbirth ratio of 161 per 1000 live births and neonatal mortality rate of 207 per 1000 live births as there were 392 live births in this cohort. Overall, the intensive care unit admission rate was 12.7% (n=52/409); moreover, 45 of 52 women (86.5%) admitted to the intensive care unit had severe maternal outcomes. The maternal death ratio was 3100 per 100,000 live births, the maternal near-miss-to-mortality ratio was 12.3, and the mortality index was 8%. CONCLUSION: Maternal near miss and maternal and perinatal mortalities were common in women with hypertensive disorders of pregnancy remote from term in referral hospitals in Ghana. Providing appropriate patient-centered and multidisciplinary quality care for these women is crucial in improving pregnancy outcomes. Context-tailored interventions should be considered in the clinical management of complications associated with hypertensive disorders of pregnancy in resource-limited settings. Further research on interventions to improve timely referral and reduce in-hospital delays in care provision is recommended to facilitate emergency care services for women with hypertensive emergencies.